Nutraceutical Potential of Carica papaya in Metabolic Syndrome - Santana, Lidiani F.; Inada, Aline C.; Espirito Santo, Bruna Larissa Spontoni do; Filiú, Wander F. O.; Pott, Arnildo; Alves, Flávio M.; Guimarães, Rita de Cássia A.; Freitas, Karine de Cássia; Hiane, Priscila A. (Nutrients, 2019)
Carica papaya L. is a well-known fruit worldwide, and its highest production occurs in tropical and subtropical regions. The pulp contains vitamins A, C, and E, B complex vitamins, such as pantothenic acid and folate, and minerals, such as magnesium and potassium, as well as food fibers. Phenolic compounds, such as benzyl isothiocyanate, glucosinolates, tocopherols (α and δ), β-cryptoxanthin, β-carotene and carotenoids, are found in the seeds. The oil extracted from the seed principally presents oleic fatty acid followed by palmitic, linoleic and stearic acids, whereas the leaves have high contents of food fibers and polyphenolic compounds, flavonoids, saponins, pro-anthocyanins, tocopherol, and benzyl isothiocyanate. Studies demonstrated that the nutrients present in its composition have beneficial effects on the cardiovascular system, protecting it against cardiovascular illnesses and preventing harm caused by free radicals. It has also been reported that it aids in the treatment of diabetes mellitus and in the reduction of cholesterol levels. Thus, both the pulp and the other parts of the plant (leaves and seeds) present antioxidant, anti-hypertensive, hypoglycemic, and hypolipidemic actions, which, in turn, can contribute to the prevention and treatment of obesity and associated metabolic disorders.